Endless History: What Hegel Could Have Learned from a Yanomami Shaman - Campello, Filipe (Revista Eletrônica Estudos Hegelianos, 2024)
How did Hegel know what Amerindians thought? Probably he had no idea. In this article, I argue that Hegel’s treatment of Amerindian peoples is rooted in an exclusionary perspective of Reason, which establishes a particular way of life as its defining standard. This stance results in a form of epistemic injustice, disregarding the possible contributions of Amerindian resources and worldviews to the lexicon established throughout modernity. To present an alternative point of view, I imagine a hypothetical dialogue between Hegel and the Yanomami shaman Davi Kopenawa. However, instead of “fitting” Amerindian concepts into the philosophical vocabulary of modernity, I confront Hegelian philosophy through the lens of encounters and the epistemic recognition of those who have been denied this. By questioning notions of progress and universal reason, I suggest that Hegel’s philosophy of history could have taken a different path had it not been entangled in a self-centered epistemic structure.
Keywords: Epistemic Injustice; Anticolonialism; Rationality; History; Progress